An infant presenting with failure to thrive and hyperkalaemia owing to transient pseudohypoaldosteronism: case report. (2nd October 2018) - De Clerck, Marieke; Vande Walle, Johan; Dhont, Evelyn; Dehoorne, Joke; Keenswijk, Werner
Abstract: A 3-month-old boy presented with failure to thrive and a history of a prenatally detected unilateral hydroureteronephrosis which was confirmed after birth. His growth and developmental milestones had been normal during the first 2 months but in the third month his appetite was poor with reduced intake but no vomiting. At presentation, his temperature was normal, there was mild dehydration and there was weight loss (his weight had decreased by 270 g in the past month). Haemoglobin was 11.9 g/dL, total white cell count 20.2 × 10 9 /L (7–15) [neutrophils 30% (39–75) and lymphocytes 61% (16–47)], platelets 702 × 10 9 /L (150–450), BUN12.1 mmol/L (2.1–16.1), serum creatinine 35.4 μmol/L (15.0–37.1), sodium 126 mmol/L (135–144), potassium 6.8 mmol/L (3.6–4.8), chloride 88 mmol/L (98–106) and bicarbonate 14 mmol/L (19–24). Intravenous rehydration with sodium chloride 0.9% solution was commenced and he was transferred to the paediatric intensive care unit. A salt-wasting syndrome was suspected and a differential diagnosis included adrenal insufficiency, pseudohypoaldosteronism and congenital adrenal hyperplasia (owing to 21-hydroxylase deficiency). Urinalysis confirmed a urinary tract infection. Serum aldosterone was 3608 ng/dL (3.7–43.2), plasma renin activity > 38.9 pmol/L (<0.85), random cortisol 459 nmol/L (74–289), adrenocorticotropic hormone (ACTH) 6.01 pmol/L (1.32–6.60) and 17-hydroxyprogesterone 4.01 nmol/L (<3.2). Treatment of the urinary tract infection was followed by normalisation of serum electrolytes and other biochemical abnormalities, return of appetite and normal growth, which confirmed the diagnosis of transient pseudohypoaldosteronsim (TPHA). TPHA is discussed and insight provided to enable early recognition and adequate treatment of this rare clinical entity.